1992
DOI: 10.1017/s0950268800049748
|View full text |Cite
|
Sign up to set email alerts
|

Apramycin resistance plasmids inEscherichia coli: possible transfer toSalmonella typhimuriumin calves

Abstract: SUMMARYAn outbreak of salmonellosis in calves was monitored for persistence of Salmonella typhimurium excretion in faeces and the effect of treatment with apramycin. Prior to treatment apramycin-resistant Escherichia coli were present but all S. typhimurium isolates were sensitive. Following the treatment of six calves with apramycin, apramycin-resistant S. typhimurium were isolated from two treated calves and one untreated calf. Plasmid profiles of E. coli and S. typhimurium were compared and plasmids conferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 12 publications
1
27
0
Order By: Relevance
“…These were chosen because all the apramycin-resistant E. coli isolated by the authors fromn pigs and calves showied cross resistance to gentamicini [3].…”
Section: Aiat1erials And) Method)smentioning
confidence: 99%
See 2 more Smart Citations
“…These were chosen because all the apramycin-resistant E. coli isolated by the authors fromn pigs and calves showied cross resistance to gentamicini [3].…”
Section: Aiat1erials And) Method)smentioning
confidence: 99%
“…uriumn of bovine origin is a common food poisoning pathogen in man. Hunter and co-workers [3] have subsequently described the presence of the same apramycin resistance plasmid in E. coli and S. typhinruriium in an outbreak of salmonellosis in calves. Transfer of the plasmid from E. coli to S. typhiniurrirun may have occurred during treatment of the calves with apramycin.…”
Section: In'trodu( Ti()nmentioning
confidence: 98%
See 1 more Smart Citation
“…The AAC(3)-IV enzyme modifies apramycin in addition to GEN. Apramycin is used exclusively in veterinary medicine, but the GEN-related chemical structure and the mobility of the aac3-IV gene inside plasmids may have contributed to the selection and dissemination of these strains in a human environment (17).…”
mentioning
confidence: 99%
“…However, there is a growing concern over the extensive use of medication in the livestock industry. One concern is the opportunity for the development of antibiotic resistant pathogens and also the antibiotic residues left in animal products intended for human consumption (Chee-Sanford et al, 2001;Dowson et al, 1994;Hunter et al, 1992). The study revealed a significant reduction in monthly antibiotic expenses after implementing the HACCP system on dairy farms.…”
Section: Discussionmentioning
confidence: 94%